PERAN PEMERINTAH DALAM PENGELOLAAN BANK SAMPAH DI KECAMATAN TEBINGTINGGI KABUPATEN KEPULAUAN MERANTI TAHUN 2023 - Kholisa, Nurul; ,, Adlin (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2025)
This study was motivated by a government policy regarding a program called the Waste Bank. This study was conducted in Tebing Tinggi District, Meranti Islands Regency, Number 2 of 2020 concerning Waste Management. The formulation in this study is how the government plays a role in managing the Waste Bank, which is one of the alternatives for waste management in Indonesia. The research used by the author is field research. This study uses the theory of the Role of Government by Ryaas Rasyid (2010), which includes 1) the role of government as a regulator, 2) the role of government as a dynamizer, 3) the role of government as a facilitator, and 4) the role of government as a catalyst. This study uses a descriptive qualitative approach. The data collection techniques used by the author are interviews, documentation, and literature study. In this study, the data analysis technique used is qualitative, based on the data obtained. The data collection techniques are conducted through interviews and document searches. Meanwhile, the data analysis techniques used are data collection, data reduction, data presentation, and conclusion drawing or verification. The results of this study found that the Meranti Islands Regency Regional Regulation No. 2 of 2020 concerning waste management is an amendment to Meranti Islands Regency Regional Regulation No. 8 of 2018, The implementation of Regional Regulation No. 2 of 2020 concerning waste management in Tebing Tinggi District, Meranti Islands Regency, in 2023 shows that the local government has carried out these four roles, although there are still various obstacles in its implementation. As a regulator, the government has issued a decree on the establishment of a waste bank, but it has not been accompanied by clear guidelines, technical guidelines, and SOPs. As a facilitator, the government provides infrastructure, but not comprehensively, especially in the procurement of the main equipment, namely shredders. As a dynamizer, socialization and recycling competitions are held, but they are not yet carried out regularly and comprehensively. As a catalyst, the government strives to build collaboration with the community and educational institutions, although cross-sector partnerships are not yet optimal. Keywords: Role of Government, Waste Bank, Regulation, Community Participation